Testicular teratoma in scrotal trauma: a case report - Anguiano-García, Sergio A.; Ledesma-Blanhir, Andrea (International Surgery Journal, 2023)
Testicular teratoma as first described by Virchow in 1863 may be one of the oldest known tumours. Patients usually course asymptomatic, early signs consist of testicular enlargement. We present a case of a male patient in his fourth decade of life with no prior documentation of testicular enlargement, he suffers from scrotal trauma presenting, pain, dysuria, scrotal swelling and nausea. Tumoral markers were normal and ultrasound revealed right testicle with cystic degeneration and malignant aspect. Radical orchiectomy was performed revealing a pure testicular teratoma. This disease may change its presentation, and there’s no prior report of diagnose after trauma, so understanding the disease, symptoms, sings and tools for diagnose may help to provide an appropriate management.